ETHNOBOTANICAL STUDY OF PANDANACEAE BY THE BESEMAH TRIBE, LAHAT DISTRICT, SOUTH SUMATERA PROVINCE - Nina Tanzerina; Harmida Harmida; Dwi Apriliani (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2022)
The research entitled Ethnobotanical study of Pandanaceae by the Besemah tribe in Lahat Regency, South Sumatra has been conducted form October 2018 to December 2019. The objective of the research were to inventory the species diversity of Pandanaceae and its traditional utilization by the local ethnic in the studied area. The research was conducted by using survey method and field work to collect plant samples. The basic data of ethnobotany was collected by using direct interview from respondents. The result showed that there were six (6) species of Pandanaceae such as; Pandanus lais Kurz, Pandanus helicopus Kurz, Pandanus amaryllifolius Roxb. (two varieties; “large and small” size fragrant pandanus), Benstonea atrocarpa Griff, Benstonea affinis Kurz. and Freycinetia rigidifolia Hemsl. 71,4% of them were belonged to wild species and 28.8% were cultivated species. The trdaitional utilization of Pandanaceae was used for handycrafft (36.4%), building material (9,1%), medicinal & cosmetic ingredients, foodstuffs and customary materials (18.2% each). The Baeemah tribe was used leaves (75%) rather than other part of plant.